Assessment of the University on the Air (UOA) as a tool of technology transfer on corn production in the Province of Iloilo - Ogatis, James Earl E. (University of the Philippines in the Visayas, 2005)
This study was conducted to assess the effectiveness of the University on the Air (UOA) on corn production as one of the tools of technology transfer in the Province of Iloilo. The UOA was conducted from September to November 2004 by the Regional Agriculture and Fisheries Information Division (RAFID) of the Dept. of Agriculture, Regional Field Unit (DA-RFU) 6 at DYRI from 4:00 to 4:30 in the morning from September to November 2003. The study used the descriptive research design and the data collected were analyzed using frequency, mean, and percentages. The sample population of this study had been chosen from among the corn farmer-enrollees from the municipalities of Tubungan and Dingle, Iloilo ; these two towns has the biggest number of UOA farmer-enrollees. The respondents were asked to rate the appropriateness, effectiveness, clarity, adoptability of each aspect on corn technology. They were requested to answer questions pertaining to their demographic profile, socio-economic status and over-all assessment of the program. The results showed that most of the farmer-student-respondents were female aging 31 to 40 years old, married, and have one to five members in the family. They were high school graduates serving as farm laborer and some were self-employed earning P5,000 to P10,000 per month. They had from two point one (2.1) to three (3) hectares of farm lands, but one point one (1.1) to two (2) hectares of these were tilled as shared tenants and devoted to corn production. As a whole, the respondents agreed that the UOA was indeed an effective tool for technology transfer on corn production as shown by very satisfactory rating of the program. It has also helped alleviate their economic conditions because of their increased income due to adoption of the new corn technology. It is recommended that future UOA shall be aired over the radio station which has high listenership rating in the region during a primetime schedule for one hour. A variety of topics loan sources and government support programs must be revise and improve in order for farmer students to understand. Likewise, feedbacks from the farmer-students must be constantly solicited for clarification of certain topics and improvement of the program.